The distributional impact of tax and benefit systems in six African countries - Katrin Gasior; Chrysa Leventi; Michael Noble; Gemma Clare Wright; Helen Barnes (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper assesses the effects of public policies on income taxes and benefits in six African countries. The comparative analysis focuses on the distribution and composition of incomes and assesses the effect of these policies on inequality and poverty. The results are based on newly developed microsimulation models for Ethiopia, Ghana, Mozambique, South Africa, Tanzania, and Zambia. They highlight differences in tax and benefit systems among these African countries, show the extent (or lack) of support available for different population sub-groups, and disentangles the redistributive impact of various income components.
Keywords: C15; H24; I3; N37; 330; Africa; tax-benefit systems; poverty; income inequality; microsimulation